Social networks and the national identity of Algerian youth: the formation of an independent identity or the embodiment of an alienated identity? - DERNOUNI, Houda (Social Sciences Journal)
This study aims to indicate whether the contribution of social networks in shaping and reshaping the national identity of Algerian youth, who interact in the social areas of special cultural contents and quality lives up to the formation of an independent national identity able to choose the production and influence, or that their interaction in these areas is the interaction consumer product identity expatriate.